Internalisation of Local Wisdom Values in the Hapakat Traditional House: Civic Character Formation and National Identity Strengthening - Aditya Fauzianur; Iqbal Arpannudin (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
Research on local wisdom has tended to focus on descriptive cultural aspects, resulting in little integrative study of the relationship between local wisdom, civic character formation, and strengthening national identity. This study aims to analyze the process of internalizing local wisdom values in the Hapakat Traditional House, its role in shaping civic disposition, and its implications for strengthening national identity. The study used a qualitative approach with an ethnographic type conducted in Penyang Village, East Kotawaringin Regency, Central Kalimantan. Data were obtained through in-depth interviews, participant observation, and documentary analysis involving the head of the Perajah Motanoi Community, community members, and members of the community who understand the existence of the Hapakat Traditional House. Data analysis was conducted using the interactive model of Miles et al. (2014) through data reduction, data presentation, and conclusion drawing. The findings reveal that the internalization of local wisdom values occurs through the interpretation of architectural symbols, socio-cultural practices, the role models of traditional leaders, deliberation activities, traditional rituals, and intergenerational interactions that instill the values of Pahari, Handep, Barendeng, Belom Bahadat, Belom Harati, Pangaji, Bakena, and Hapakat Kula, a set of Dayak ethical principles concerning kinship, mutual aid, civility, and communal harmony. These values contribute to shaping civic dispositions in the form of responsibility, discipline, social awareness, tolerance, mutual cooperation, awareness of rules, deliberation skills, and commitment to the common good. The implications of this research demonstrate the growth of national awareness rooted in the preservation of local culture through the integration of Dayak cultural values with Pancasila values (Indonesia's five foundational state principles).